GREEN PRACTICES IMPLEMENTATION AND SUSTAINABILITY CHALLENGES IN BALI'S HOTEL INDUSTRY: INSIGHTS FROM HOTEL OPERATORS - Siti Muamalah; Bussagorn Leejoeiwara (POLITEKNIK LP3I JAKARTA, 2026)
As one of the world's leading tourism destinations, Bali faces increasing environmental pressures resulting from rapid tourism development. In response, many hotels have adopted green practices to support sustainable tourism; however, the implementation of such initiatives remains uneven across the hospitality sector. This study explores how green practices are implemented within Bali's hotel industry and examines the challenges faced by hotel operators in maintaining sustainability initiatives. A qualitative research approach was employed using semi-structured interviews with four hotel representatives, including managers from both eco-certified and non-eco-certified hotels in Bali. Data were analyzed using thematic analysis to identify recurring patterns and key themes related to sustainability implementation and operational challenges. The findings reveal significant variation in the adoption of green practices among hotels, with common initiatives including waste reduction programs, energy conservation measures, water-saving practices, and efforts to reduce single-use plastics. Hotel operators reported several barriers to effective implementation, including high operational costs, limited technical support, inconsistent government enforcement, and varying levels of environmental awareness among tourists. The findings also indicate differences in sustainability expectations between domestic and international tourists, with international visitors generally demonstrating stronger environmental awareness. In addition, participants highlighted the importance of transparent sustainability communication and the growing role of social media in shaping tourists' perceptions of environmentally responsible accommodation. This study contributes to the sustainable tourism literature by providing industry-based insights into the practical realities of implementing green initiatives in Bali's hospitality sector.